PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS OF FORMATION OF TOLERANCE TO WORK IN THE CONDITIONS OF INCLUSIVE EDUCATION - Zalanovskaya, Lesya (PSYCHOLOGICAL JOURNAL, 2019)
The article is related to the concept of tolerance, as a positive reaction to the existence of differences; social property, a means of achieving social consent; one of the principles of humanistic education. The essence of the education of tolerance is the deliberate formation of a positive (overcoming negative) experience of tolerance, that is, the creation of space for direct or indirect interaction with others in the views or behavior of people, their communities. It is noted that the educational strategy should ensure the creation of such pedagogical conditions that promote the formation of tolerant beliefs, attitudes and skills of tolerant behavior in the family, educational institution, in the future professional activity involving all interested persons (parents, teachers, social workers, politicians, means the media and society as a whole). It is noted that the process of integration of children with special needs into the general education space will be successful only in conditions of professional competence of teachers of educational institutions and the creation of a comfortable, inclusive, tolerant educational environment in which the child integrates. Consequently, the formation of tolerant consciousness in modern youth occurs both in the process of learning, and in non-auditing work. The methodological basis for the formation of tolerance is: personal, competency and activity approaches to learning. The psychological and pedagogical conditions of the formation of tolerance in the conditions of inclusive education are presented, which consist in the development of the professional and personal readiness of the future teacher to work in the conditions of inclusion, namely, in development: 1) the cognitive component, namely, the expansion of the general outlook of students and the provision of a high level of professional knowledge enabling a deeper understanding of the person's mental and behavioral characteristics; 2) the emotional component, namely, the education of students on the principles of respectful and benevolent attitude towards the personality of each person, the development of their sense of responsibility for their actions and the development of empathic understanding of another person, which reveals opportunities for sympathetic attitude towards it, and thus becomes the basis of tolerance ; 3) the conative (behavioral) component of tolerance, that is, through practical exercises and games that enable the ability to work out the skills and skills of professional communication on the basis of a tolerant attitude; 4) the personal component of tolerance, which involves the formation of value orientations, the adoption of a tolerant culture as a value necessary for interaction with other people; the development of emotional balance, which makes it possible to maintain a certain orientation of their actions in an emotional situation using self-control and thereby contribute to professional success. It was revealed that the introduction of a model of tolerance formation and its efficiency in a higher educational establishment can be ensured if: – the formation of tolerance is part of the general system of professional training of students, aimed at the development of professional-personality new formations, implemented in educational work with students; – the psychological and pedagogical conditions necessary for the fullest implementation of the program of tolerance formation are created; – problematic discussions are organized, in which experience takes into account other points of view, which activates the development of the mechanism of decentralization; – the process of reflection is organized.